The Influence of Motivation and Work Commitment on Employee Performance at PT. PDAM South Kalimantan and Central Kalimantan Palangka Raya Area - Ferdinand (Indonesian Journal of Advanced Research, 2023)
Research in the field of human resource management, aims to improve employee performance at PT. PDAM Region of South Kalimantan and Central Kalimantan of Palangka Raya Area. The research theory used is organizational culture which will have an impact on organizational effectiveness with the influence of motivation and work discipline. The research method uses an explanatory approach with survey techniques, the number of samples in this study was 40 respondents, and was analyzed by SEM PLS. The results showed that the influence of significant positive motivation of 48.2% in improving performance. Motivation to work discipline is significantly positive at 62% and work discipline is significant positive at 43.5% to employee performance at PT. PDAM (Persero) for South Kalimantan and Central Kalimantan in the Palangka Raya area. The implications of research results can improve organizational culture for organizational effectiveness by increasing the elements/variables of motivation and performance discipline. Further research can examine the value of strategic cultural change to improve employee performance.